Liquid-crystal display 3D printing of hierarchical SiC structures with tunable porosity via pickering emulsion - Pung, Kah Sheng (Nanyang Technological University, 2023)
Hierarchically porous ceramics such as silicon carbide (SiC) offer unique microstructures and properties, allowing their use in various applications. However, the shaping of these porous ceramics into complex geometries remains extremely challenging. Emerging additive manufacturing technologies such as vat photopolymerization could enable the freeform fabrication of hierarchically porous SiC ceramics. In this work, a SiC-based Pickering emulsion was developed and optimized for the vat photopolymerization of porous SiC ceramics. Various surfactants and the compositions of the Pickering emulsions were investigated, and their effects on the microscale porosity (~10 – 50 μm) of the green bodies revealed. The prepared Pickering emulsions were printed on a commercially available liquid crystal display (LCD) printer, highlighting the feasibility and viability of vat photopolymerization of these Pickering emulsions. Various optimization methods were explored to enhance print adhesion, and the curing properties of these Pickering emulsions were revealed. Subsequently, debinding and sintering of the SiC green bodies were performed successfully. The sintered SiC ceramics possessed microscale pore sizes of 6.22 ± 0.89 μm, low bulk densities of 33.3%, good compressive strength of 4.45 ± 0.96 MPa, and specific strength of 4.16 x 103 Nm kg-1. These properties were comparable to that of conventionally prepared porous SiC, which highlights the suitability of using Pickering emulsions for the vat photopolymerization of hierarchically porous SiC ceramics.